Modulating work-hardening behaviors and tensile plasticity of in-situ formed ductile dendrite Ti-based bulk metallic glass composites with tailored dendrite composition. (15th March 2018) - Liu, Dingming; Zhu, Zhengwang; Li, Zhengkun; Zhang, Long; Fu, Huameng; Wang, Aimin; Li, Hong; Zhang, Hongwei; Wang, Yandong; Zhang, Haifeng
Abstract: A novel series of in - situ dendrite Ti-based bulk metallic glass composites (BMGCs) were obtained. The Mo content of the dendrites monotonically increases from nil to 10.5 at% while the dendrite volume fraction and the composition of the amorphous matrix remain nearly invariant. It was found that the mechanical behaviors varied tremendously simply by changing the Mo content. Thus, the correlation between the composition and the mechanical behaviors under tension has been determined for in - situ dendrite Ti-based BMGCs for the first time. Graphical abstract: Image 1